Is there a cortical blood flow redistribution pattern related with perspective error in schizophrenia? - Ortuno, Felipe (Array, 2009)
We studied relative cortical blood flow (relCBF) patterns associated to correct performance (CP) and perseverative error (PE) during Wisconsin Card Sorting Test (WCST) execution, in controls and patients with schizophrenia.Patients made significantly more PE than controls during WCST performance. In patients, we found a significant correlation between PE and relCBF in right occipital cortex. In controls, we found a significant correlation between CP and relCBF of several cortical regions during WCST execution: left orbitofrontal cortex and left global frontal cortex positively and parietal bilateral cortex negatively. The severity of PE during WCST performance is associated to a low left frontal-temporal activity in controls and to a high right parietal-occipital activity in schizophrenia